Vessel use at the Mycenaean Palace of Ayios Vasileios, Laconia, using Organic Residue Analysis - Spiteri, Cynthianne; Kardamaki, Eleftheria; Becher, Julia; Belser, Matthias; Fratucello, Lioba; Heikkilä, Raija Katarina; Labra-Odde, Catalina; Mathur, Arvin Raj; Mittelstädt, Katja; Jung, Reinhard (Prähistorische Zeitschrift, 2024)
In Mycenaean palaces a wide range of consumption activities took place, from the most exclusive to mass-consumption. Here we apply organic residue analysis to a typologically wide ceramic assemblage from the Mycenaean palace of Ayios Vasileios (early fourteenth to mid thirteenth century BC), and the succeeding settlement of the early twelfth century BC, with the aim of investigating the functions of common shapes and to observe patterns of chronological and spatial differentiation related to the palatial and post-palatial phases, the first study of its kind for a Mycenaean palace.